Orbital transfer vehicle (OTV) system sizing study for manned GEO satellite servicing. (20th April 2016) - Chudoba, B.; Coleman, G.; Gonzalez, L.; Haney, E.; Oza, A.; Ricketts, V.
ABSTRACT: In an effort to quantify the feasibility of candidate space architectures for astronauts servicing Geosynchronous Earth Orbit (GEO) satellites, a conceptual assessment of architecture-concept and operations-technology combinations has been performed. The focus has been the development of a system with the capability to transfer payload to and from geostationary orbit. Two primary concepts of operations have been selected: (a) Direct insertion/re-entry (Concept of Operations 1 – CONOP 1 ); (b) Launch to low-earth orbit at Kennedy Space Center inclination angle with an orbital transfer to/from geostationary orbit (Concept of Operations 2 – CONOP 2 ). The study concludes that a capsule and de-orbit propulsion module system sized for the geostationary satellite servicing mission is feasible for a direct insertion/re-entry concept of operation CONOP 1 . Vehicles sized for CONOP 2 show overall total mass savings when utilising the aero-assisted orbital transfer vehicle de-orbit propulsion module options compared to the pure propulsive baseline cases. Overall, the consideration of technical, operational and cost factors determine if either the aero-assisted orbital transfer vehicle concepts or the re-usable/expendable ascent/de-orbit propulsion modules is the preferred option.